2010
DOI: 10.1007/s11095-010-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Cetirizine Degradation Product: Mechanism of Cetirizine Oxidation

Abstract: Degradation of cetirizine in polyethylene glycol arose from the reaction between the drug and the reactive peroxide intermediates such as peroxyl radicals formed through oxidation of PEG. Selective oxidation of cetirizine and isolation/characterization of the oxidation product allowed the identification of the oxidation product as cetirizine N-oxide. The mechanism of oxidation is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…1(a), the product was identified as cetirizine N-Oxide. Similar product was predicted by other author (Dyakonov et al, 2010) when cetirizine was oxidized by H 2 O 2 .…”
Section: Kinetic Measurementssupporting
confidence: 89%
“…1(a), the product was identified as cetirizine N-Oxide. Similar product was predicted by other author (Dyakonov et al, 2010) when cetirizine was oxidized by H 2 O 2 .…”
Section: Kinetic Measurementssupporting
confidence: 89%
“…The interaction between Cetirizine with excipients of polyols has been reported previously . A PEG‐containing matrix was used for Cetirizine formulation in order to develop the highly water‐soluble and sensitive compound in soft gelatin dosage form that has already been found to be unstable during manufacture and storage …”
Section: Resultsmentioning
confidence: 91%
“…The short chain aldehydes may form hydroxymethyl derivative of the formulated compound and cross‐link amino groups containing compounds, while carboxylic acids may lower the pH of PEG solution and can degrade compounds susceptible to acid catalyzed hydrolytic degradation . The degradation of cetirizine hydrochloride to N ‐oxide impurity was attributed to the presence of peroxides in the formulation originating from autoxidation of PEG 400 . In another study, Fukuyama et al reported significant racemization of cholecystokinin (formation of undesired R‐enantiomer) receptor antagonist due to the presence of formic acid in PEG 400 formulation .…”
Section: Fabrication Of Redox‐responsive Nanogelsmentioning
confidence: 99%